2003
DOI: 10.1086/376619
|View full text |Cite
|
Sign up to set email alerts
|

Cholera, Diarrhea, and Oral Rehydration Therapy: Triumph and Indictment

Abstract: Cholera drove the sanitary revolution in the industrialized world in the 19th century and now is driving the development of oral rehydration therapy (ORT) in the developing world. Despite the long history of cholera, only in the 1960s and 1970s was ORT fully developed. Scientists described this treatment after the discovery of the intact sodium-glucose intestinal cotransport in patients with cholera. This new understanding sparked clinical studies that revealed the ability of ORT to reduce the mortality associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 64 publications
0
88
0
4
Order By: Relevance
“…Vibrio cholerae is a pathogenic bacterium which may cause the severe diarrheal disease 20 cholera [1]. As an adaptation for growth at high NaCl concentrations, V. cholerae expels 21 sodium ions from the cytoplasm during respiration and establishes a sodium motive force 22 across its inner membrane [2].…”
Section: Introduction 19mentioning
confidence: 99%
“…Vibrio cholerae is a pathogenic bacterium which may cause the severe diarrheal disease 20 cholera [1]. As an adaptation for growth at high NaCl concentrations, V. cholerae expels 21 sodium ions from the cytoplasm during respiration and establishes a sodium motive force 22 across its inner membrane [2].…”
Section: Introduction 19mentioning
confidence: 99%
“…The present first-line treatment is oral rehydration therapy with salt and sugar, believed to have been first used in 1960. 1 John Drysdale (1816-1890), the influential editor of the British Journal of Homoeopathy, published an analysis of a series of 175 cholera patients whom he had treated homeopathically in Liverpool in 1849. 20 He allowed his patients to drink as much water as they wanted, following the lead of John MacKintosh, a colleague of Latta at the Drummond Street Hospital.…”
Section: Maintaining Hygiene and Hydrationmentioning
confidence: 99%
“…History tells us that the bacterial cause was not understood until 1883, and the gold standard treatment of oral rehydration therapy was first used in 1960. 1 Of the six 19th-century cholera pandemics, the third, in 1849-1860, resulted in the most fatalities. In Great Britain, there were 23,000 deaths, 10,000 in London alone.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no evidence that individuals with type 1 diabetes are at increased risk for traveler's diarrhea, infection and dehydration in diabetic individuals increases blood glucose levels and more commonly results in hospitalization than in normal individuals (76). Furthermore, it has been reported that many diabetic people inappropriately refrain from treating their diarrhea with oral rehydration solutions that contain carbohydrate (75), a widely used substrate to enhance sodium absorption (77). However, one very small study on this topic demonstrated only nonsignificant increases in blood glucose levels in patients taking oral rehydration solutions that contained either glucose or rice, suggesting that such preparations can be safely used by patients with type 1 All medications should be in appropriately labeled (e.g.…”
Section: Additionalmentioning
confidence: 99%